Analyzing the effect of customer loyalty on virtual marketing adoption based on theory of technology acceptance model - Peyman Ghafari Ashtiani; Atefeh Parsayan; Moein Mohajerani (Management Science Letters, 2016)
One of the most advantages of the internet and its expansion is probably due to its easy and low cost access to unlimited information and easy and fast information exchange. The accession of communication technology for marketing area and emergence of the Internet leads to creation and development of new marketing models such as viral marketing. In fact, unlike other marketing methods, the most powerful tool for selling products and ideas are not done by a marketer to a customer but from a customer to another one. The purpose of this research is to analyze the relationship between customers' loyalty and the acceptance of viral marketing based on the theory of technology acceptance model (TAM) model among the civil engineers and architects who are the members of Engineering Council in Isfahan (ECI). The research method is descriptive–survey and it is applicable in target. The statistical population includes civil engineers and architects who are the members of Engineering Council in Isfahan including 14400 members. The sample size was determined 762 members based on Cochran sampling formula, the sample was selected as accessible. The data was collected by field method. Analyzing the data and recent research hypothesis, the data was extracted from the questionnaires. Then, all the data was analyzed by computer and SPSS and LISREL software. According to the results of the data, the loyalty of the civil engineers and architects members of ECI was associated with the acceptance and practical involvement of viral marketing.